2020
DOI: 10.1371/journal.pone.0230202
|View full text |Cite
|
Sign up to set email alerts
|

Can optical flow perturbations detect walking balance impairment in people with multiple sclerosis?

Abstract: People with multiple sclerosis (PwMS) who exhibit minimal to no disability are still over twice as likely to fall as the general population and many of these falls occur during walking. There is a need for more effective ways to detect preclinical walking balance deficits in PwMS. Therefore, the purpose of this study was to investigate the effects of optical flow perturbations applied using virtual reality on walking balance in PwMS compared to age-matched controls. We hypothesized that susceptibility to pertu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 53 publications
(70 reference statements)
2
8
1
Order By: Relevance
“…multiple sclerosis (MS; n = 37), clinically isolated syndrome (CIS; n = 2)). Whereas previous studies identified this gait parameter as important hallmark of MS-related gait deficits 37 , 51 , 52 there are, to our knowledge, no findings that related enhanced step width variability with increased risk of falls in patients with MS or CIS.…”
Section: Discussioncontrasting
confidence: 59%
“…multiple sclerosis (MS; n = 37), clinically isolated syndrome (CIS; n = 2)). Whereas previous studies identified this gait parameter as important hallmark of MS-related gait deficits 37 , 51 , 52 there are, to our knowledge, no findings that related enhanced step width variability with increased risk of falls in patients with MS or CIS.…”
Section: Discussioncontrasting
confidence: 59%
“…First, our sample size was relatively small (11 and 14 for controls and PwMS respectively). This sample size was chosen based on: (1) our previous work [ 53 ] investigating differences in standing balance and visual oscillations between controls and PwMS, in which sample sizes of 10 and 10, respectively, produced significant results; (2) published work [ 17 ] which reported that visual perturbations during gait produce a significant difference between controls and PwMS with a sample size of 14 and 14; and (3) despite our small sample size we obtained adequate effect sizes and relatively high power (on average > 0.85). However, we do suggest that given the nonhomogeneous nature of MS, the results may have limited applicability to cases that differed from our sample and a larger group may be needed for broader interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…The response to visual oscillation, referred to as visuomotor entrainment, characterizes the ability to synchronize or adapt motor responses to a visual stimulus [ 30 ]. Visual field-of-view oscillations and their resulting effect on sway and foot placement have been used to demonstrate increased reliance on vision with age [ 31 ] and MS [ 8 , 17 ]. Interestingly, the effect of object motion within a scene, which places additional demands on visual processing of movement, has not been studied in PwMS.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PwMS have altered temporalspatial gait patterns [6] as well as increased variability of trunk movement [7] and footfall placement variability [8] during gait, all of which are expected to contribute to the increased likelihood of balance loss and falls [9][10][11][12]. To compensate for the impact of the loss in proprioception on balance, PwMS might have greater reliance on the vestibular or visual systems for balance control [13], as documented by a decrease in stability when visual feedback is removed during standing [14][15][16] and increased sensitivity to visual stimuli during gait [17]. Because of the potential increased importance of vision on gait stability in PwMS, the effects of visual perturbations of different types on body sway and foot placement during gait were examined in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The response to visual oscillation, referred to as visuomotor entrainment, characterizes the ability to synchronize or adapt motor responses to a visual stimulus [30]. Visual eld-of-view oscillations and their resulting effect on sway and foot placement have been used to demonstrate increased reliance on vision with age [31] and MS [8,17]. Interestingly, the effect of object motion within a scene, which places additional demands on visual processing of movement, has not been studied in PwMS.…”
Section: Introductionmentioning
confidence: 99%